Mobile Passport as One of the Bureaucratic Reform Strategies at the Special Class I Immigration Service in Surabaya - Widyawati Widyawati; Achmad Wahyu Deby Leksono; Amirul Mustofa; Eny Haryati (Jurnal Hukum, Administrasi Publik dan Negara, 2025)
This study aims to describe and analyze: the application of the MPaspor application as one of the bureaucratic reform strategies and the supporting and inhibiting factors for the implementation of the M-Passport application as one of the bureaucratic reform strategies in the Special Class 1 Immigration Office of the City of Surabaya. The research method to be used is qualitative descriptive. Data Collection Techniques include: Interviews, Observations, Documentation. The research informant is the Head of the Suarabaya Special Class I Immigration Office. The data analysis technique using interactive model analysis was developed by Miles et al., (2014), namely data condensation, data presentation, and conclusion drawn. The results of the study show . Mobile Passport as one of the Bureaucratic Reform Strategies at the Surabaya Special Class I Immigration Office is carried out based on the Institutional Aspect, namely the M-Passport Application based on the Letter of the Director of Immigration Traffic Number IMI.2-UM.01.01-4.0700 dated February 18, 2022 concerning the Follow-up of the Implementation and Implementation Policy of Mobile Passport (M-Paspor) at Immigration Offices throughout Indonesia. In terms of bureaucratic reform, M Passport services in the institutional field, office employees must have proficiency, that is, each office employee must be able to master the skills and knowledge needed in serving citizens, especially foreign citizens who take care of ITAS and ITAP. In terms of resources, it is already available and given full support with the availability of competent IT experts to support the development and implementation of the M-Passport application. The Financial Resources provided continue to be provided for the launch, maintenance, and renewal of the M-Passport application. In terms of governance, as a Technical Implementation Unit of the Special Class I Immigration Office of Surabaya by paying attention to the provision of facilities to support the running process of a bureaucracy. The Surabaya Special Class I Immigration Office provides a guarantee of passport processing time by officers during the interview session, photo taking, and fingerprint scanning for three working days. Passport application service fee Passport costs Rp 350,000, while electronic passport costs Rp 650,000. One of the supporting factors for the implementation of the M Passport Application at the Surabaya Special Class I Immigration Office is supporting facilities and infrastructure, such as queue machines, service counters, and computers. Inhibiting factors include application servers that often crash or have problems. In addition, there is a lack of public understanding that in taking care of passports, original documents must still be brought.